2008
DOI: 10.3402/fnr.v52i0.1857
|View full text |Cite
|
Sign up to set email alerts
|

Observed dietary intake in adults with intellectual disability living in the community

Abstract: Background: Knowledge is lacking about dietary habits among people with intellectual disability (ID) living in community residences under new living conditions. Objective: To describe the dietary habits of individuals with ID living in community residences, focusing on intake of food, energy and nutrients as well as meal patterns. Design: Assisted food records and physical activity records over a 3-day observation period for 32 subjects. Results: Great variation was observed in daily energy intake (4.9Á14 MJ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 20 publications
(29 reference statements)
7
64
0
9
Order By: Relevance
“…The results from the participant observations that were directed to the social aspects on meals are reported elsewhere (Adolfsson, Mattsson Sydner, and Fjellströ m, forthcoming). Main results from the assisted food records describing individual dietary habits, focusing on food and meal patterns as well as on energy and nutrients have been reported earlier (Adolfsson et al 2008).…”
Section: Methodsmentioning
confidence: 95%
“…The results from the participant observations that were directed to the social aspects on meals are reported elsewhere (Adolfsson, Mattsson Sydner, and Fjellströ m, forthcoming). Main results from the assisted food records describing individual dietary habits, focusing on food and meal patterns as well as on energy and nutrients have been reported earlier (Adolfsson et al 2008).…”
Section: Methodsmentioning
confidence: 95%
“…vegetables is generally below that found in the general population (Adolfsson et al, 2008) adding further insult to bone integrity.…”
Section: Dietary Interventions For Bone Health In People With Learninmentioning
confidence: 69%
“…Studies on dietary intakes of people with a learning disability have reported an increase in snacking between meals as well as an increased consumption of bread, cakes, meat products and milk and reduced consumption of fruit and vegetables compared to the general population (Adolfsson et al 2008). This is corroborated by recommended daily intakes and biochemical markers of micronutrients not meeting the recommended amounts (Hoey et al 2016).…”
Section: Anti-oxidants and Polyphenolsmentioning
confidence: 96%